Prevalence of breast-related symptoms, health care seeking behaviour and diagnostic needs among women in Burkina Faso - Ströbele, Leonie Isabel Luna; Kantelhardt, Eva Johanna; Traoré Millogo, Timongo Francoise Danielle; Sarigda, Maurice; Wacker, Jürgen; Grosse Frie, Kirstin (BMC public health, 2018)
Breast Cancer, Cancer early detection, Sub-Saharan Africa, Health care seeking behavior, Health care system